Capaian standar pelayanan minimal gizi di Rumah Sakit Umum Daerah (RSUD) Manokwari Papua Barat - Nurhasanah Mardianingsih; Fasty Arum Utami; Ika Ratna Palupi (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2020)
Achievement of the nutrition minimum service standard at Manokwari District Hospital in West PapuaBackground: There are three indicators of nutrition services that are regulated in the hospital Minimum Service Standards (MSS), namely the timeliness of food distribution, patient's plate waste, and the accuracy of the patient’s diet. The achievement of minimum service standards as the indicator of quality for nutrition services at Manokwari District Hospital has not yet been known.Objective: To find out the implementation of minimum service standards for nutrition services,i.e. the promptness of food distribution, the proportion of plate waste, and accuracy of the patient’s diet at Manokwari District Hospital. Methods: This was a mixed-method study conducted at Manokwari District Hospital, West Papua, from January until March of 2018. A quantitative approach with patient samples was carried out to quantify the achievement of MSS for nutrition service. Punctuality of food distribution and accuracy of the diet was measured using observational sheets while the patient’s plate waste was determined using food weighing. A qualitative approach through in-depth interviews with patients, nutritionists, cooks, food service workers, and nurses was performed to explore the influencing factors. Results: The percentage of timeliness of patient food distribution was only 37.1%, the waste of patients’ food reached 34.5% and the accuracy of the patient's diet was only 83.87%. These were affected by poor human resource management, inadequate hospital facilities, and foods brought from outside of the hospital. Conclusions: Promptness of patient’s food distribution, plate waste and diet accuracy in Manokwari District Hospital has not reached the minimum service standard for nutrition service.